Eighth Graders’ Communication Strategies in English Classroom Activities at SMP Negeri 3 Kalibening - Adityas Purwaningsih; Darmahusni (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2021)
This study aimed to investigate the eighth graders’ communication strategies in English classroom activities at SMP Negeri 3 Kalibening. This research conducted a qualitative approach with a descriptive method. The observational data were collected by using a video and audio recorder, observational sheet, and triangulated by structured interview. The data analysis procedures consisted of data reduction, data display, and conclusion drawing and verification by Miles & Huberman’s (1994) framework. The Communication Strategies (CSs) taxonomy proposed by Celce-Murcia et al. (1995) was used as references to identify and classify types of CSs. The analysis revealed that the learners employed 5 types of CSs: avoidance or reduction strategy, achievement or compensatory strategy, stalling or time gaining strategy, self-monitoring strategy, and interactional strategy, with 11 sub-types of those categories in classroom discussion, group discussion, and group presentation activities. The findings also showed that the learners employed CSs to compensate for their linguistics problems and keep the communication going while participating in English classroom activities. This research made a valuable contribution in introducing communication strategies and increasing students' awareness to use English in real-life situations.